GSH-resistant and highly cytoselective ruthenium(ii)-p-cymene-(imidazo[4, 5-f][1, 10]phenanthrolin-2-yl)phenol complexes as potential anticancer agents. Issue 30 (26th July 2021) - Kar, Binoy; Das, Utpal; De, Sourav; Pete, Sudhindra; Sharma S, Ajay; Roy, Nilmadhab; S. K., Ashok Kumar; Panda, Debashis; Paira, Priyankar
Abstract : Ruthenium(ii )- p -cymene-imidazophenanthroline complexes were developed as highly cytoselective and GSH-resistant anticancer agents against HeLa and Caco-2 cell lines. Abstract : To avoid the side effects of the current popular platinum-based anticancer drugs, researchers have made tireless attempts to design appropriate GSH-resistant Ru(ii )-arene complexes. In this regard, luminescent ruthenium(ii )- p -cymene-imidazophenanthroline complexes were developed as promising highly cytoselective cancer theraputic agents for HeLa and Caco-2 cells.